Optimizing Guideline-directed Medical Therapies for Heart Failure with Reduced Ejection Fraction During Hospitalization - Neal M Dixit; Shivani Shah; Boback Ziaeian; Gregg C Fonarow; Jeffrey J Hsu (US Cardiology Review)
Heart failure remains a huge societal concern despite medical advancement, with an annual direct cost of over $30 billion. While guideline-directed medical therapy (GDMT) is proven to reduce morbidity and mortality, many eligible patients with heart failure with reduced ejection fraction (HFrEF) are not receiving one or more of the recommended medications, often due to suboptimal initiation and titration in the outpatient setting. Hospitalization serves as a key point to initiate and titrate GDMT. Four evidence-based therapies have clinical benefit within 30 days of initiation and form a crucial foundation for HFrEF therapy: renin-angiotensin-aldosterone system inhibitors with or without a neprilysin inhibitor, β-blockers, mineralocorticoid-receptor-antagonists, and sodium-glucose cotransporter-2 inhibitors. The authors present a practical guide for the implementation of these four pillars of GDMT during a hospitalization for acute heart failure.